Housing in the context of economic restructure - Moraes Valença, Márcio (2001)
The main objective of this article is to analyse the housing market and policy in the context of globalisation. It aims, therefore, to identify the relevant processes that are established between the international economic system and the national systems, in order to verify its effects on public policy and the housing market. Globalisation, which has led to rapid transformations on the political and international economics scene, is a fundamental concept to explain the recent changes taking place in public policy - in this case housing policy - in countries of distinct characteristics that differ in the global context. The article focuses on three distinct contexts: Brazil, from the Figueiredo government, with the worsening of the external deficit crisis, to the first government of president Fernando Henrique Cardoso; Great Britain, from the ascension of the ultra-conservative Margaret Thatcher who, halfway through a crisis of fordism, inverted the logic of public policy operations and carried out profound economic, political and institutional reforms, until the beginning of Tony Blair's Labour government; and Portugal, the post-colonial period when, liberated from the dictatorship, the country was able to carry out real institutional reforms, including joining the EEC in 1986, and which have had a profound effect on its socio-politico-economic profile. The general reference context of the study is the post-war period of development and, in particular, the 1980s and 1990s.